NATURAL CONVECTION ON CORRUGATED PLATES: A NUMERICAL CASE STUDY ABOUT MESHES, BOUNDARY CONDITIONS AND PHYSICAL DOMAIN DETERMINATION - Verdério Júnior, S. A.; Scalon, V. L.; Oliveira, S. R.; Martins Coelho, P. J. (Revista de Engenharia Térmica, 2022)
The transfer of heat and mass by natural convection is present in the most diverse physical and chemical phenomena of nature and engineering equipment. In the last decades, the number of research on natural convection has grown dramatically, highlighting studies in physical-mathematical modeling and numerical solutions, experimental analysis and design and optimization techniques for fluid-thermal systems. This case study analyzed the influence of several numerical parameters in physical-mathematical modeling and numerical solution of natural convection heat transfer problems on isothermal plates with square waves in turbulent conditions of high Rayleigh number. The numerical parameters analyzed were the mesh refinement degree, wall boundary conditions (with or without wall functions implemented in the turbulent parameters) and computational physical domain influence. Free and open-source computational numerical tools were exclusively used in the construction of this work. Meshes with wall functions implemented in turbulent parameters presented greater accuracy and required less computational effort and simulation time, besides enabling the use of a lower degree of mesh refinement. The best numerical configuration of the physical model for the situation problem studied were defined from the criteria of accuracy, computational effort demanded, and stability and numerical convergence of the solution.